2017
DOI: 10.7205/milmed-d-16-00282
|View full text |Cite
|
Sign up to set email alerts
|

Streamlining Participant Recruitment for TBI and PTSD Research Studies

Abstract: Collaborative work with multiple disciplines and institutions, and the use of diverse media, was critical to augmenting participant enrollment, and significantly diversified the demographics of the participant population. Streamlining the referral process helps studies meet their timelines and target enrollment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Yaffe et al have shown that military personnel with PTSD are twice as likely to develop dementia as those without PTSD [ 10 ]. TBI and PTSD are highly comorbid conditions in civilian life and among veterans [ 7 , 9 ], and both conditions are associated with an increased risk of developing dementia later in life [ 5 ]. This link between TBI and PTSD may result from the physical injury and consequent cognitive impairments arising from TBI [ 33 ], or may be due to persistent trauma-related memory [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yaffe et al have shown that military personnel with PTSD are twice as likely to develop dementia as those without PTSD [ 10 ]. TBI and PTSD are highly comorbid conditions in civilian life and among veterans [ 7 , 9 ], and both conditions are associated with an increased risk of developing dementia later in life [ 5 ]. This link between TBI and PTSD may result from the physical injury and consequent cognitive impairments arising from TBI [ 33 ], or may be due to persistent trauma-related memory [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is increasingly recognized that traumatic brain injury (TBI) and posttraumatic stress disorder (PTSD) increase the risk of cognitive decline and dementia [ 5 , 6 ], suggesting a link with AD. In addition, there is considerable comorbidity of PTSD with TBI in both civilian and military settings [ 7 9 ], which raises the possibility of synergistic effects favouring the risk of dementia.…”
Section: Introductionmentioning
confidence: 99%
“…This suitability aspect of screening was important to ensure client wellbeing, and aligned with previously reported safety considerations to exclude clients based on the risk of stress-related reactions in a comparable study of CA use for participants with dementia. 28 Challenges recruiting clients with TBI 29 and stroke 30 for clinical research have been previously reported. Similarly, a scoping review of studies of CAs for participants with brain-related conditions revealed low sample sizes: for example, a CA study for severe TBI had one participant, 31 and research of CAs for dementia have had one participant, 32 five participants 33 and 28 participants.…”
Section: Discussionmentioning
confidence: 99%
“…First, despite considerable efforts, the oneyear follow-up rate of recruited patients was relatively low at 38%. The difficulties in recruitment in TBI studies are a subject addressed in a growing body of literature with proposed solutions to be implemented in the future, [64][65][66] because this low recruitment rate can introduce a bias in the results and weaken the development of knowledge within the field. Second, we used psychomotor vigilance testing to assess mean reaction time.…”
Section: Study Limitationsmentioning
confidence: 99%